1995
DOI: 10.1007/bf00217421
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of bdellovibrios from submerged surfaces and other aquatic habitats

Abstract: The distribution of bdellovibrios was investigated over a wide geographical area of the Chesapeake Bay including some tributaries and subestuaries. Bdellovibrios were recovered from five aquatic habitats; water, sediment, oyster shell surface biofilm, zooplankton, and plants over a wide range of temperature and salinity measurements. Consistently, the greatest number of the predators was recovered from samples of biofilm irrespective of temperature and salinity. A decrease in the numbers and frequency of preda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
42
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 10 publications
2
42
0
Order By: Relevance
“…After their initial discovery, Bdellovibrios were isolated from various habitats and found to be widely distributed in aquatic and terrestrial environments (6)(7)(8)(9). Since its discovery and up to the time of writing this review, more than 390 articles have been published concerning this bacterium and similar organisms.…”
Section: Historical Perspective the Early Years (1962-1992)mentioning
confidence: 99%
“…After their initial discovery, Bdellovibrios were isolated from various habitats and found to be widely distributed in aquatic and terrestrial environments (6)(7)(8)(9). Since its discovery and up to the time of writing this review, more than 390 articles have been published concerning this bacterium and similar organisms.…”
Section: Historical Perspective the Early Years (1962-1992)mentioning
confidence: 99%
“…However, they can also be found in fresh and brackish water, sewage, water reservoirs, and seawater (16,17,34). Another environmental niche with which bdellovibrios have been associated are biofilms (18,48). It is believed that biofilms might offer good conditions for bdellovibrios' survival since these organisms have been found in natural marine biofilms but are not always recovered from the surrounding water (17,18,48).…”
mentioning
confidence: 99%
“…Another environmental niche with which bdellovibrios have been associated are biofilms (18,48). It is believed that biofilms might offer good conditions for bdellovibrios' survival since these organisms have been found in natural marine biofilms but are not always recovered from the surrounding water (17,18,48). It is suggested that in a biofilm bdellovibrios can benefit from higher prey density, which has been shown to be necessary for Bdellovibrio survival (19,44).…”
mentioning
confidence: 99%
“…They can also be found in freshwater, brackish water, seawater, sewage, water pipes, and water reservoirs (13,22). It has been shown that marine Bdellovibrio species preferentially associate with surfaces, where they are components of biofilms (13,31).The biphasic growth cycle of Bdellovibrio species includes a free-swimming attack phase and an intraperiplasmic growth phase; this growth cycle distinguishes this group of bacteria from all other bacterial parasites of bacteria (29). Three Bdellovibrio species, Bdellovibrio bacteriovorus, Bdellovibrio stolpii, and Bdellovibrio starrii, were described first on the basis of their GϩC contents and DNA relative association data (23, 26) and then on the basis of 16S rRNA analysis data (6).…”
mentioning
confidence: 99%
“…They can also be found in freshwater, brackish water, seawater, sewage, water pipes, and water reservoirs (13,22). It has been shown that marine Bdellovibrio species preferentially associate with surfaces, where they are components of biofilms (13,31).…”
mentioning
confidence: 99%